From the "Nova Brasília Favela" case to the "Jacarezinho Community" case: Police violence, mutilated citizenship and necropolitics - Mota , Maria Nazareth Vasques; Mota , Guilherme Gustavo Vasques; Rubim , Larissa Campos (Seven Editora, 2023)
In this article, cases of police violence are reported, repeatedly perpetrated in State police operations, under the justification of combating drug trafficking, in poor communities, in the midst of the so-called "war on drugs", with a deadly effect on individuals who even have passage through the police. Such police operations were prohibited, in the face of the Corona Virus Epidemic, by the decision of Minister Edson Fachin, in ADPF, however, they continued to be perpetrated, reaching communities that are not even consistent with the criminal practice of drug trafficking and have their dignity offended, as the materialization of the right to decent housing can be gauged by the respect that the State bestows on those it must treat as citizens. The approach methodology was inductive, starting from specific situations to general conclusions, the method of procedure was historical and descriptive, and the techniques used were bibliographical and documental, with the use of newspaper works and the internet. After three sections, it was concluded by understanding that the way of combating drug trafficking has been implemented as war, but who die are blacks, poor people and people in vulnerable and risk situations, stripped of citizenship and targets of true necropolitics. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-135